Do you want to be told if you have cancer? A cross-sectional survey of Ghanaians - Elliot A. Asare; Alisha Lussiez; Melissa H. Watt; Charles K. Dally; Eileen A. Micah; Gifty Kwakye (Journal of Global Health Reports)
# Background